Industrial boiler ash as an alternative for reducing formaldehyde emissions in medium-density fiberboards - Bayestorff da Cunha A.* (2024)
© 2024 Informa UK Limited, trading as Taylor & Francis Group.The study aimed to determine the feasibility of utilizing industrial boiler ash in the production of medium-density fiberboard, to reduce formaldehyde emissions without compromising physical and mechanical properties. Panels were manufactured with a density of 750 kg.m−³, employing 12% urea-formaldehyde resin and 1% paraffin emulsion, both with and without an ammonium sulfate-based catalyst. The production process involved cold pre-pressing followed by hot pressing at 180 °C and 40 kgf.cm−² for 10 min. The experimental plan varied in terms of the percentages of ash added to the adhesive (0%, 1%, 3%, and 5%) and the application of the catalyst. Both the properties of the adhesives and the panels were assessed. It became evident that both the catalyst and ash altered the adhesive properties. Regarding panel properties, the ash reduced formaldehyde emissions, but the catalyst had a more pronounced effect. The catalyst's impact on moisture content, bending strength (MOR), and modulus of elasticity (MOE) was observed, whereas ash positively influenced dimensional stability at 5% levels but adversely affected internal bond.